Toward Prevention and Control of Type 2 Diabetes: Challenges at the U.S.-Mexico Border and Beyond - Barbara A. Bowman, PhD; Frank Vinicor, MD, MPH (Centers for Disease Control and Prevention, 2005)
Type 2 diabetes makes a compelling case study for public health action (1). The disease respects no boundaries. It is increasingly common occurring in both developed and developing countries (2), in men and women, at earlier ages than in past decades, and in persons of every race and ethnic group, with a high prevalence in Hispanic/Latino Americans and in other minority groups, including non-Hispanic blacks, American Indians, Alaska Natives, Asian Americans, and Native Hawaiian and other Pacific Islanders (3). As noted by Martorell (4) and Saldaña (5), family history and genetic factors appear to further increase the risk for type 2 diabetes in Hispanic/Latino Americans. In the United States, the prevalence of diabetes was estimated to be 18.2 million people (6.3% of the population) in 2002 (3), with dramatic increases predicted in the future (6). The determinants of type 2 diabetes are largely understood. Two of the most important risk factors, obesity and physical inactivity, are modifiable. The natural history involves progression from prediabetes, a condition in which blood glucose metabolism is abnormal (although not yet in the diabetes range), to the development of type 2 diabetes. The rate of progression from prediabetes to type 2 diabetes is between 3% and 10% per year (7). However, progression from prediabetes to diabetes can be prevented or delayed with sustained weight loss and increased physical activity (8,9). The magnitude of the change needed for primary prevention of type 2 diabetes is relatively modest: a 7% to 10% weight loss and sustained moderate physical activity, at least 30 minutes per day (10). Today, the number of adults with prediabetes in the United States is estimated to be at least 41 million (3).